Use of decision trees to detect if a room is occupied using Python - Atamari Aguilar, Joel (2022)
This article presents a description of the decision trees for determining whether a room is occupied or not. In this research it is empirically demonstrated that it is possible to determine whether a room is occupied or not, using the variables temperature, humidity, luminosity, CO2 level and the humidity ratio, by using decision trees with the SKLEARN libraries in the language Python.